An Appraisal of Michel Foucher's African Borders: Putting Paid to a Myth. Issue 2 (14th March 2020) - Asiwaju, Anthony I.
ABSTRACT: This review interrogates the apparently colonialist apology in the argument by the author of the publication under scrutiny, that the boundaries of independent African state territories, within and especially externally, are, after all, not the European contraptions they have hitherto been presumed in existing works. It argued in support of the status quo, that the boundaries are, in the main, European impositions, inherited with little or no modifications by the inheritance elites as at the at the dates of the independences.